A testudinid herpesvirus 1 (TeHV1)-associated disease outbreak in a group of Horsfield’s tortoises (Testudo horsfieldii) - Schüler, Lisa; Picquet, Pierre; Leineweber, Christoph; Dietz, Janosch; Müller, Elisabeth; Marschang, Rachel E. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
In spring 2020, a severe disease outbreak with high morbidity and mortality was observed in a collection of 15 Horsfield’s tortoises (Testudo horsfieldii). Affected tortoises showed upper respiratory- and gastrointestinal tract signs, including rhinitis and stomatitis. Testudinid herpesvirus 1 (TeHV1) and Mycoplasma spp. were detected by PCR in oral swabs of affected animals. Histological examination of one deceased animal showed intranuclear inclusion bodies typical for herpesvirus infections in liver, spleen and oesophagus. The virus was likely introduced into the collection 2 years earlier by a clinically healthy Horsfield’s tortoise that was tested positive for TeHV1 by PCR.
Keywords: Tortoise; herpesvirus; mycoplasma; stomatitis; skin lesions; latency